Modular wireless trackside signalling system: towards Rail Internet of Things (RIoT) - Mendez Villalon, Armando (2020)
Railway operations are becoming increasingly automated and integrated through the use of Information and Communication Technology. Advance signalling systems efficiently handle the traffic among a railway network providing the ability to increase the population of rolling stock on the same track with a precise time slot for each of them, as well as diminishing risks by human error.